Effects of straw incorporation and straw-burning on aggregate stability and soil organic carbon in a clay soil of Bangladesh - Halder, Milton; Ahmad, Shahnewaz Jim; Rahman, Tanvir; Joardar, Jagadish Chandra; Siddique, Md. Abu Bakar; Islam, Muhammad Saiful; Islam, Mahbub Ul; Liu, Shuai; Rabbi, Sheikh; Peng, Xinhua (Geoderma Regional, 2023)
The clay soil of Bangladesh is typically low in soil organic carbon (SOC) and generally has poor soil aggregate stability (measured as mean weight diameter, MWD). The addition of organic amendments in the field has the potential to increase soil organic matter (SOM) and MWD. However, the influence of organic amendments on aggregation in the clay soils of Bangladesh is largely unknown. A short-term (105 days) field study has been conducted to evaluate the effects of straw incorporation and straw-burning treatments on MWD and SOC in clay soil under eggplant (Solanum melongena L.). This study consisted of three treatments: (i) control (no amendments), (ii) rice straw (straw applied at 21 t ha−1), (iii) rice straw-burning (ash retained after burning at 7.4 t ha−1). Soil samples were collected after plant harvest, and then MWD, SOC, glomalin-related soil protein (GRSP), microbial biomass carbon (MBC), Fe-oxides, and available soil nutrients (e.g., N, P, K, S, Na, Ca, and Mg) were determined. Our results showed that MWD in straw addition treatment was on average 2 times higher, whereas SOC was 1.3 times higher compared to the control and straw-burning treatments, respectively (P < 0.05). Conversely, the straw-burning treatment reduced the MWD by 19% and the SOC by 20% compared to the control treatments (P < 0.05). Significant improvements in the available K, S, and Mg content of soil were found in the straw incorporation treatment (P < 0.05). We did not find any significant influence of the treatments on the MBC and GRSP content of the soil. Soil organic carbon had a significant correlation with MWD (R2 = 0.80**, P < 0.01), while GRSP and Fe-oxides did not show any relationship with MWD (P > 0.05). Our study demonstrates that the incorporation of rice straw has the potential to increase soil aggregation and SOC stock, at least for the short term in the clay soils of Bangladesh. •Straw incorporation increased the MWD and SOC compared to straw-burning and control.•Straw-burning reduced the MWD and SOC compared to the control.•SOC was increased with increasing aggregate size.•Straw incorporation and straw-burning did not influence MBC, GRSP, and amorphous Fe-oxide.•SOC played a major role to increase aggregation in the clay soils of Bangladesh.